Pengaruh Pemanfaatan Chatgpt sebagai Media Komunikasi Digital terhadap Kepercayaan Diri Akademik dan Prestasi Akademik Mahasiswa - Diva Trisha Venia; Mazdalifah Mazdalifah; Nurbani Nurbani (KOLONI, 2026)
This study aims to analyze the influence of ChatGPT utilization as a digital communication medium on students’ academic self-confidence and academic achievement at Universitas Medan Area. This research employed a quantitative approach within a positivist paradigm. The population consisted of 12,613 students from the 2022 cohort of Universitas Medan Area, while the sample included 400 respondents selected using the Slovin formula and purposive sampling. Data were collected through a Likert-scale questionnaire and analyzed using simple linear regression, correlation coefficient, and coefficient of determination. The instruments were reliable, with Cronbach Alpha values of 0.834 for ChatGPT utilization, 0.808 for academic self-confidence, and 0.728 for academic achievement. The results show that ChatGPT utilization has a positive and significant effect on academic self-confidence, with the equation Y1 = 22.914 + 0.352X, R = 0.416, R² = 0.173, and p < 0.001. ChatGPT utilization also has a positive and significant effect on academic achievement, with the equation Y2 = 17.990 + 0.247X, R = 0.361, R² = 0.130, and p < 0.001. These findings indicate that ChatGPT can function as a supportive learning communication medium that strengthens students’ academic confidence and learning outcomes, although its contribution is not yet dominant because other factors remain outside the research model.